MINAT BELAJAR BAHASA JEPANG PADA COSPLAYER DI PEKANBARU - Rike Amelia; Merri Silvia Basri; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the interest in learning Japanese languageamongcosplayers in Pekanbaru. The research is a type of descriptive qualitative reseach with theinstrument used was interviews with 4 informans. The results of this study indicate thet on average,people who cosplay are also interested in learning Japanese language from listening to andwatching anime.Key words: Cosplay,Japanese Language,Cosplayer